2007
DOI: 10.4028/www.scientific.net/msf.539-543.119
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and Mechanical Properties of Twin-Roll Strip Cast Mg Alloys

Abstract: Development of wrought Mg alloys, particularly in sheet form, is essential to support the growing interest for lightweight components in the automotive industry. However, development of Mg alloy sheets has been quite slow due to the complexity of sheet production originated from limited deformability of Mg. In this respect, twin-roll strip casting, a one-step processing of flat rolled products, can be an alternative for the production of Mg alloy sheets. In this study, AZ31 and experimental ZM series alloys ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 30 publications
0
6
0
1
Order By: Relevance
“…A reduction in the centerline segregation has been also reported as a result of annealing [5]. Fine equiaxed grains with an average size of 6 m are produced via TRC followed by warm rolling and annealing [5,[21][22]24,27]. Recently, the present authors have observed texture alteration upon postannealing of the TRC sheet [25].…”
Section: Introductionmentioning
confidence: 54%
See 1 more Smart Citation
“…A reduction in the centerline segregation has been also reported as a result of annealing [5]. Fine equiaxed grains with an average size of 6 m are produced via TRC followed by warm rolling and annealing [5,[21][22]24,27]. Recently, the present authors have observed texture alteration upon postannealing of the TRC sheet [25].…”
Section: Introductionmentioning
confidence: 54%
“…The AZ31B alloy (supplied by Timminco, now Applied Magnesium) was melted in a graphite crucible using a NORAX induction furnace under a gas mixture of sulfur hexafluoride (SF 6 ) and carbon dioxide (CO 2 ). A plate with a thickness of 4 mm was cast at 720 • C into a vertical copper die and at a cooling rate close to that experienced during the TRC process, i.e., ∼185 • C/s [21,23,27].…”
Section: Methodsmentioning
confidence: 99%
“…11 The tensile properties of TRC Mg alloy sheets are comparable with or better than those of Mg alloy sheets produced by conventional ingot casting and the subsequent complicated rolling process. 12,13 Although most TRC Mg alloys, either commercial or experimental, do not contain RE elements, the use of RE elements in conventionally produced Mg sheet alloys appears to be unavoidable at present when formability and isotropic mechanical properties are concerned due to the significant effect of RE elements on randomising and weakening the basal texture. [14][15][16][17] The amount of RE elements in most of these alloys ranges from 1 to 3 wt-% and therefore the increase in raw material cost by using RE elements would not be significant at present.…”
Section: Costmentioning
confidence: 99%
“…There are worldwide a small number of industrial or laboratory scale twin roll casters installed at universities, companies and research facilities. Initial results from these activities on conventional wrought and cast alloys have shown promising sheet properties [2][3][4][5][6]. Former results indicate that the processing parameters of twin roll casting have a significant influence on the microstructure and texture of the strips [7].…”
Section: Introductionmentioning
confidence: 98%